Attachment insecurity hinders cardiac patients' ability to receive partners' care: A longitudinal dyadic study. (May 2020) - George-Levi, Sivan; Peleg, Shira; Vilchinsky, Noa; Rafaeli, Eshkol; Khaskiaa, Abid; Mosseri, Morris; Hod, Hanoch
Objectives: The fact that spousal support is not always beneficial for the recipient continues to intrigue researchers in the dyadic support field. One possible explanation for this phenomenon may be individual differences in attachment orientations, which might promote or, conversely, hinder the ability to capitalize on one's partner's support. We therefore assessed the interactive contribution of cardiac patients' attachment orientations (anxious and avoidant) and partners' caregiving styles (sensitive and compulsive) to patients' anxiety symptoms 6 months after a first acute coronary syndrome (ACS). Design and methods: A longitudinal design was employed among 114 couples coping with one partner's ACS. During hospitalization, patients completed the Experiences in Close Relationships scale, tapping attachment orientation, and 6 months later, the anxiety scale of the Brief Symptom Inventory. Partners completed the Adult Caregiving Questionnaire during patients' hospitalization. Results: Regression analyses showed that partners' caregiving styles moderated the positive association between patients' anxious attachment and anxiety symptoms. This association was stronger when partners were characterized with high levels of compulsive caregiving, but also, and surprisingly, when partners were characterized with high levels of sensitive caregiving. No significant effects were found for highly avoidant patients. Conclusions: The findings suggest that patients' personalities play a crucial role in determining the consequences of partners' caregiving styles. Integrating the personality perspective into the dyadic paradigm may allow a more comprehensive understanding of the circumstances under which partners' care reduces patients' distress.